Roger Jones family papers - Jones, Elizabeth Cocke Pratt, 1701-1762.; Jones, Frederick, -1722.; Jones, Roger, 1625?-1701.; Jones, Thomas, -approximately 1757.; Jones, Thomas, 1726-approximately 1785.; Jones, Thomas, -approximately 1800.; Jones, Thomas ap Thomas, 1782-1843.; Jones, Walter, 1745-1815.
Correspondence, memoranda, diaries, notebooks, legal documents, financial records, printed matter, survey plats, and other papers. Chiefly the papers of the descendants of Captain Roger Jones who accompanied Thomas Culpeper, Baron Culpeper, to Virginia in 1680. Chronicles the lives of several generations of Jones family members in Virginia, North Carolina, and Kentucky. Subjects include family affairs; Virginia agriculture, commerce, courts, slave holdings, and tobacco plantations; and genealogical matters. Includes papers of the allied Catesby and Pratt families. Correspondents include William Campbell Preston Breckinridge, William Byrd, Robert Carter, Mark Catesby, Charles Goore, Patrick Henry, Elizabeth Catesby Cocke Holloway, L.H. Jones, Walter King, Thomas Knox, Stephen R. Mallory, William Molleson, Laurence Muse, Thomas Nelson, John Pratt, James Russell, and John Warden; and the firms, Bogle & Scott and Farell & Jones.
Microfilm edition of Series 1 and 2 available
Microfilm produced from originals in the Manuscript Division.
Family members represented include Roger Jones' sons, Frederick Jones of North Carolina and Thomas Jones (died circa 1757) and his wife, Elizabeth Cocke Pratt Jones; Thomas' sons, Walter Jones, physician and member of Congress, and Col. Thomas Jones (1726-circa 1785) of Northumberland County, Va.; Major Thomas Jones (died circa 1800) of Henrico County, Va., son of Col. Thomas Jones; and his son Thomas ap Thomas Jones of Clark County, Ky.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Breckinridge, William Campbell Preston, -- 1837-1904 -- Correspondence; Byrd, William, -- 1674-1744 -- Correspondence; Carter, Robert, -- 1663-1732 -- Correspondence; Catesby, Mark, -- 1683-1749 -- Correspondence; Culpeper, Thomas, -- Baron Culpeper, -- 1635-1689.; Goore, Charles, -- 1701-1783 -- Correspondence; Henry, Patrick, -- 1736-1799 -- Correspondence; Holloway, Elizabeth Catesby Cocke -- Correspondence; Jones, L. H. -- Correspondence; King, Walter -- Correspondence; Knox, Thomas, -- active 1758 -- Correspondence; Mallory, Stephen R. -- 1813-1873 -- Correspondence; Molleson, William, -- 1732 or 1733- -- Correspondence; Muse, Laurence -- Correspondence; Pratt, John -- Correspondence; Russell, James -- Correspondence; Nelson, Thomas, -- 1738-1789 -- Correspondence; Warden, John -- Correspondence; Catesby family; Jones family; Pratt family; Agriculture -- Virginia; Courts -- Virginia; Plantations -- Virginia; Slavery -- Virginia; Tobacco -- Virginia; Clark County (Ky.) -- Social life and customs; Henrico County (Va.) -- Social life and customs; Kentucky -- Genealogy; Kentucky -- Social life and customs; North Carolina -- Genealogy; North Carolina -- Social life and customs; Northumberland County (Va.) -- Social life and customs; Virginia -- Genealogy; Virginia -- Social life and customs